A Framing Analysis of the Treatment of Creativity as a Topic or Goal in German Books on Research Writing - Peters, Ingo (Journal of Academic Writing, 2018)
Many students in Germany undertaking academic writing tasks consult one of the numerous German-language books on research writing. Curiously, these works tend to downplay or ignore creativity, compared to their American counterparts. A hermeneutic and rhetorical study that examines the structure, content, and style of 21 German books on research writing with the help of framing theory reveals that, firstly, the rationale given to readers for learning how to do a research project is usually that it enables them to complete difficult tasks and thus to graduate successfully – the potentially fascinating aspects, such as learning through writing, and the possibility of advancing the field are rarely mentioned. Secondly, when defining good academic research, US books stress exploration and invention based on wrestling with questions, while the German ones mostly emphasize rules, correctness within a fixed system, and the mastery of techniques. Finally, in the 21 works, academic work primarily comes across as a solitary, linear process neatly divided into separate phases, not as a holistic, discursive practice that takes place within the research community. The likely reasons for this phenomenon highlight several crucial challenges German writing teachers and consultants are facing: as the rhetoric/composition and writing consultancy scene in Germany is vibrant but somewhat marginalized at universities and relatively new, there is no tradition of mandatory composition courses influenced by writing studies with a creative component, and most guidebooks on research are not by writing experts but by professors in other fields. Moreover, there is still widespread belief that creativity cannot be taught, and that students’ fascination with their chosen field of study should be taken for granted, so that neither need to be mentioned in primers. Terminology might also play a role; the German term for ‘research (writing)’, ‘Wissenschaftliches Arbeiten’ or ‘academic practice’, already appears to emphasize correctness over discovery.